Factor Structure of the Short Form of the Zarit Burden Inventory (ZBI-12) Among Iranian Family Caregivers of Patients Undergoing Hemodialysis: A Methodological Study - Moslemi, Fatemeh; Mirhosseini, Seyedmohammad; Sharif-Nia, Hamid; Ebrahimi, Hossein; Abbasi, Ali (Shahroud Journal of Medical Sciences, 2025)
Background: Measuring the amount of caregiving burden is crucial, considering the significant role of family caregivers in promoting the health of patients undergoing hemodialysis treatment. One of the most commonly used tools for assessing caregiver burden is short form of the Zarit Burden Inventory (ZBI-12). This study aimed to evaluate the psychometric properties of the ZBI-12 in family caregivers of patients undergoing hemodialysis in Iran.Methods: The present study was a cross-sectional methodological study involving four hundred participants. The validity assessment of ZBI-12 was carried out in three stages: face validity, content validity and construct validity. Additionally, convergent and discriminant validity were examined, followed by assessing reliability.Results: During the Exploratory Factor Analysis, two factors were identified: caregiver-related and patient-related concerns. These factors accounted for 56.7% of the total variance in care burden. Confirmatory Factor Analysis validated all goodness-of-fit indices of the final model. Two factors of this inventory demonstrated high internal consistency (Cronbach's alpha coefficient = 0.90 and 0.79; McDonald's omega coefficient = 0.902 and 0.843) and stability (Intraclass Correlation Coefficient = 0.95 and 0.96), respectively.Conclusion: Based on the findings of the present study, it can be concluded that the Persian version of the ZBI-12, consisting of 12 items and two factors, is a practical and valuable tool for measuring the care burden of family caregivers in the hemodialysis treatment.